APPLICATION OF NEW ION-EXCHANGE MATERIAL FOR SORPTION OF NICKEL IONS (Scientific journal of the Fergana State University, 2025)
The article studies the physicochemical properties of the new ion-exchange material PPM-1 in order to determine its application areas. The nature of the functional groups of the PPM-1 sorbent was analyzed using IR spectra and potentiometric titration. The kinetics of nickel ion adsorption on the PPM-1 sorbent under static conditions was studied.